Saudi Arabia and Iran : volatile political geography of oil and minorities - James, M. Dorsey (2015)
The political geography of oil and minorities in Saudi Arabia and Iran highlights a fault line in the Sunni-Shiite divide at the core of violent transition in the Middle East. Disgruntled minorities demanding greater rights and an end to repression populate the oil-rich regions of the two countries that are the major protagonists in the Middle East's sectarian divide.